The Relationship Between Learning Discipline And Learning Achievements Of Eleventh Grade Students Of Adisutjipto Flight Vocational High School Yogyakarta Of Academic Year Of 2020/2021 - Dewi, Yunita Ari Puspita (SOLUTION, 2020)
This research is started from field data in which phenomena in Adisutjipto Flight Vocational High School Yogyakarta have caught the researcher’s attention. The phenomena are expulsion from school, school truancy, grade retention. Therefore, this research aims to find out the relationship between learning discipline and learning achievements.    This research was quantitative research using a correlational approach. The research subject was 192 students of the eleventh grade of Adisutjipto Flight Vocational High School Yogyakarta of the academic year of 2020/2021. The research data collection used was a questionnaire with two types of the instrument of data collection namely Learning Discipline Scale and Test of 15 courses in the form of multiple choice. The research data analysis technique was correlated using the Pearson product-moment formula.The research result shows that there is a correlation between learning discipline and learning achievements with a correlation value of 0.234. In addition, this result indicates an accepted hypothesis. Even though the correlation is low, it still has a relationship between learning discipline and learning achievements of eleventh-grade students of Adisutjipto Flight Vocational High School Yogyakarta of the academic year of 2020/2021. The analysis technique used was a correlation of Pearson product-moment.